2022
DOI: 10.1038/s41398-022-01844-x
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota and plasma cytokine levels in patients with attention-deficit/hyperactivity disorder

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is a common childhood mental disorder with undetermined pathophysiological mechanisms. The gut microbiota and immunological dysfunction may influence brain functions and social behaviours. In the current study, we aimed to explore the correlation of gut microbiome imbalance and inflammation in the pathophysiology of ADHD. Forty-one children with ADHD and thirty-nine healthy-control (HC) individuals were recruited. Faecal samples from all participants were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 77 publications
0
25
0
Order By: Relevance
“…Meanwhile, cytokines TNF-α, IFN-γ, and IL-17 were negatively correlated with ADHD symptoms. Previous studies have also shown that TNF-αplasma levels in the ADHD group were significantly lower than those in the control group [ 33 , 34 ]. However, another study demonstrated that TNF-α did not differ significantly between the ADHD group and the control group, nor was there significant correlation with parent-assessed ADHD symptoms [ 35 ].…”
Section: Discussionmentioning
confidence: 93%
“…Meanwhile, cytokines TNF-α, IFN-γ, and IL-17 were negatively correlated with ADHD symptoms. Previous studies have also shown that TNF-αplasma levels in the ADHD group were significantly lower than those in the control group [ 33 , 34 ]. However, another study demonstrated that TNF-α did not differ significantly between the ADHD group and the control group, nor was there significant correlation with parent-assessed ADHD symptoms [ 35 ].…”
Section: Discussionmentioning
confidence: 93%
“…Alpha diversity of intestinal microbiota between the ADHD and control groups did not differ significantly in five studies [ 17 , 77 , 78 , 79 , 80 ]. One study reported decreased alpha diversity in ADHD patients, and moreover, this result negatively correlated with hyperactivity symptoms [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…Decreased levels of Faecalibacterium [ 77 , 78 ], Haemophilus [ 79 ], Prevotella , Parabacteroides [ 81 ], Lachnoclostridium, Sutterella , Dialister [ 78 ], and Veillonella [ 77 ] were reported in the ADHD group. On the other hand, elevated amounts of Agathobacter, Anaerostipes , Lachnospiraceae_UCG_010 [ 80 ], Neisseria [ 81 ], Fusobacterium [ 6 ], Ruminococcaceae_UCG_004 [ 79 ], Enterococcus , and Odoribacter [ 77 ] were observed. The genus Ruminococcaceae_UCG_004 was associated with inattention scores on the Conners Adult ADHD Rating Scales (CAARS) and Conners Teacher Rating Scale (CTRS) [ 79 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has suggested that the level of SCFAs was relevant to inflammatory bowel conditions with comorbid depression and anxiety [ 60 , 61 ]. The abundance of Agathobacter has also been determined to be associated with ADHD and sleep problems in a population with autism spectrum disorder [ 62 , 63 ]. There is a paucity of information on the role of Agathobacter in the pathophysiology of depression.…”
Section: Adjusted For Sex Age and Score Of Snap-iv Discussionmentioning
confidence: 99%